2019
DOI: 10.3892/mmr.2019.10051
|View full text |Cite
|
Sign up to set email alerts
|

TGF‑β1 promotes the osteoinduction of human osteoblasts via the PI3K/AKT/mTOR/S6K1 signalling pathway

Abstract: Transforming growth factor β1 (TGF-β1) has been suggested to be a candidate cytokine in the field of bone tissue engineering. Cytokines serve important roles in tissue engineering, particularly in the repair of bone damage; however, the underlying molecular mechanisms remain unclear. In the present study, the effects of TGF-β1 on the osteogenesis and motility of hFOB1.19 human osteoblasts were demonstrated via the phenotype and gene expression of cells. Additionally, the role of the phosphatidylinositol 3-kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 59 publications
5
46
0
Order By: Relevance
“…Consistent with our finding, the PI3K-Akt cascade has long been considered as one of the most significant Smad-independent regulatory route for MSC osteogenesis [52]. For example, Zhang et al has reported that treatment with 1 ng/mL of TGFβ1 augmented the proliferation and mineralization of human hFOB1.19 osteoblasts via the activation of PI3K-Akt [53]. On the other hand, there is also evidence of BMP9-induced enhancement of the PI3K-Akt signaling pathway in an osteo-stimulatory context.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our finding, the PI3K-Akt cascade has long been considered as one of the most significant Smad-independent regulatory route for MSC osteogenesis [52]. For example, Zhang et al has reported that treatment with 1 ng/mL of TGFβ1 augmented the proliferation and mineralization of human hFOB1.19 osteoblasts via the activation of PI3K-Akt [53]. On the other hand, there is also evidence of BMP9-induced enhancement of the PI3K-Akt signaling pathway in an osteo-stimulatory context.…”
Section: Discussionsupporting
confidence: 91%
“…Fortunately, novel-miR-3880 and siELF2 could activate PI3K/AKT/mTOR/S6K1 and Bcl2/Bax pathways, and possesses the ability to alleviate the decline of PI3K/AKT/mTOR/S6K1 phosphorylation levels and Bcl2/Bax expression ratio, which might be a reason for the mitigative effects of novel-miR-3880 and siELF2 on reduced MEC proliferation induced by PI3K, AKT, mTOR, or S6K1 inhibitor. It thus appears that the results are consistent with previous research that PI3K/AKT/mTOR/S6K1 pathway activation benefits cell growth (Park et al, 2011;Zhang et al, 2019), and provide sufficient evidence for the participation of novel-miR-3880 and ELF2 in the modulation of PI3K/AKT/mTOR/S6K1 pathway both in vitro and in vivo. In addition, the role of ciRNA13761 and DOCK1 in PI3K/AKT/mTOR/S6K1 pathway and Bcl2/Bax pathway was elaborated, which increases evidence for the regulation of ciRNA13761/novel-miR-3880/ELF2 to PI3K/AKT/mTOR/S6K1 and Bcl2/Bax pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, previous studies have investigated whether TGF‐β signaling activates PI3K/AKT pathway, either directly or indirectly, in various cell types including osteoblasts, 44 HEK293 cells, 45 prostate cancer cells, 46 and vascular smooth muscle cells 47 . The PI3K/AKT signaling pathway activation has been reported to promote Sertoli cell proliferation.…”
Section: Discussionmentioning
confidence: 99%